Promoting right to information through e-governance - A case of e-soochna and other initiatives in H.P. - Jain, Abhishek; Jain, Aarushi (2009)
The Right to Information Act, 2005 has been hailed as a landmark administrative reform unleashing an unprecedented era of transparency, accountability and efficiency in governance. E-Governance further makes Right to Information (RRI) a meaningful reality. This article details how E-Governance can accelerate the reach, impact and utility of the RTI. Scientific management of records and community informatics have been emphasised. Then the important initiatives for RTI and E-Governance at the national level, across states and concept of "E-District" have been discussed. The maximum need of RTI and E-Governance is observed at decentralised levels. In this context, a description is made of certain cutting edge initiatives undertaken in Palampur SDM office and Kullu district including `E-Soochna' and the first Right to Information Centre of Himachal Pradesh. The article ends with some suggestions to promote RTI with E-Governance. - Reproduced.
Keywords: E soochna; E governance; Right to information